Reconceptualizing Pesantren and Local Wisdom as an Ethnopedagogical Model: A Systematic Literature Review - Dewi Anggraeni; Zulkifli; Fuad Jabali (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2026)
This study aims to reconceptualize pesantren and local wisdom as ethnopedagogical models through a systematic review of academic literature published between 2015 and 2025. Using a systematic literature review guided by the PRISMA framework, this study examines Scopus-indexed articles to identify how pesantren and local wisdom are represented in the scholarly literature. It explores the foundations of ethnopedagogy, emerging research trends, thematic patterns, and pedagogical models that arise from integrating Islamic teachings with local cultural practices. The findings indicate that pesantren are increasingly understood not merely as religious educational institutions, but as culturally embedded learning ecosystems. Within these ecosystems, knowledge production, value transmission, and pedagogical practices are shaped by the interaction between Islamic epistemology, local wisdom, and lived social practices. Three interrelated pillars consistently sustain pesantren-based ethnopedagogy: culturally grounded epistemology, experiential pedagogical practices, and value-based social learning. Based on this synthesis, the study proposes a pesantren-based ethnopedagogical model that comprises an epistemological foundation, culturally embedded pedagogical practices, and the internalization of values through lived experience. The study contributes theoretically by extending ethnopedagogical discourse to religion-based education and practically by offering a conceptual framework for culturally responsive Islamic education.